Smart Hypermarket System / Fatin Zaliqha Azmy ... [et al.] - Azmy, Fatin Zaliqha; Jamaludin, Natasha; Azahari, Nurakmatul Adilla (2012)
Consisting of three main systems, the Smart Hypermarket System allows the customers to scan their own purchased items. The cashiers only need to scan the temporary receipt's barcode for the customers to make the payments. This system is unique in the sense that its inventory management system helps to update the inventory in hypermarket and at the same time give reports on the sales made by the hypermarket. A security system which can display unpaid items on the screen was also designed upon realizing the crucial need for security system in hypermarkets. This system is designed due to the arising problems in hypermarkets concerning the long queue at the cashier counters, manual inventory management and the needs for security guards to check the unpaid items manually. The Smart Hypermarket System is developed using JAVA programming language for database and inventory system and also RFID and microcontroller for the security system. Hopefully, this system will help to reduce the problems faced by hypermarkets and thus provide a more conducive environment for the benefits of all.